1992
DOI: 10.2307/3431339
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Particle Dissolution in Alveolar Macrophages

Abstract: Aerosol particles deposited in the lungs that are not reaolily soluble in the epithelial lining fluid will be phagocytized by alveolar macrophages (AM). Inside the phagolysomal vacuole, the constituents ofthe plam allow dissolution ofavaiety ofcompounds at a higher rate than dissolutionietracelular lung fluids. Cielator concentration and a pH value ofabout 5 were found to control intracellular partice dissolution (IPD). Hence, IPD is the initial step oftranslocation ofdissolved material to blood, which is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 40 publications
3
31
1
1
Order By: Relevance
“…Mechanisms have been proposed and studied in vivo for selective concentration of elements present in minerals as insoluble phosphate salts (18,19,24), and more recently, Galle tron microscopy and microanalysis the composition and morphology of dense phosphate deposits inside rat macrophages after inhalation of mineral salt-based aerosols (20). These precipitates exhibit granular morphologies not unlike those of the silica precipitates observed in the present experiments.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Mechanisms have been proposed and studied in vivo for selective concentration of elements present in minerals as insoluble phosphate salts (18,19,24), and more recently, Galle tron microscopy and microanalysis the composition and morphology of dense phosphate deposits inside rat macrophages after inhalation of mineral salt-based aerosols (20). These precipitates exhibit granular morphologies not unlike those of the silica precipitates observed in the present experiments.…”
Section: Discussionmentioning
confidence: 50%
“…One proposed mechanism is that the dust particles cause the macrophage to generate enzymes that eventually lead to its destruction and the formation of abnormal tissue in the lung (16,17). Although one of the normal mechanisms for the elimination of foreign particles relies on the capability of macrophages to dissolve solid particles of low aqueous solubility (18)(19)(20), recent studies have shown that the opposite can also occur [i.e., that the lysosome of lung macrophages may concentrate and precipitate elements inhaled as a part of water soluble compounds (21)]. …”
mentioning
confidence: 99%
“…These simulated body fluids are used to examine a variety of materials (Sun and others, 2001;Herting and others, 2006) and permit modeling of in vitro solubility, an important physiochemical factor that determines the rate and extent that particles are retained at the site of deposition, translocated to other tissues, or excreted (Kanapilly and others, 1973;Kreyling, 1992;Ansoborlo and others, 1999) relative to an inhalation pathway. The lung fluid has neutral pH; the phagolysosomal fluid models the lower pH (4.5) encountered when particles are engulfed by pulmonary alveolar macrophages, which are specialized lung cells involved in particle removal from the lung.…”
Section: Inhalation Pathwaymentioning
confidence: 99%
“…These simulated body fluids were developed and used to examine a variety of materials (Herting and others, 2006;Sun and others, 2001;Stefaniak and others, 2006), permit modeling of in vivo solubility, an important physiochemical factor that determines the rate and extent that particles are retained at the site of deposition, translocated to other tissues, or excreted (Ansoborlo and others, 1999;Kreyling, 1992;Kanapilly and others, 1973) relative to an inhalation pathway. The lung fluid has neutral pH; the PSF models the lower pH (4.5) encountered when particles are engulfed by pulmonary alveolar macrophages, specialized lung cells involved in particle removal from the lung.…”
Section: Inhalation Pathwaymentioning
confidence: 99%